Impediments to Fostering Interculturalism at Home: The Nation-State, Social Power, and Cultural Representation in EFL Teaching Materials (Comparative & International Education Series, 2021)
The present pandemic moment in which students’ international mobility is curtailed sets the stage to think about the effectiveness of local education. In this essay, I consider the role of local English language teaching (EFL) in fostering interculturalism. Reflecting on a corpus of public school EFL teaching materials from Japan collected as part of a larger, ongoing examination of the hidden curriculum, I focus on how they portray international culture. I conclude that these materials reflect historical relations of social power in placing emphasis upon powerful nations while also implicitly promoting the notion of cultural uniformity within countries, a uniformity in which the visibility of privileged social groups prevails. Both aspects – coupled with misconceptions about the nature of culture itself - are at odds with effectively fostering interculturalism. This particularly impacts students for whom the EFL class may represent the primary channel for intercultural opportunity in lieu of international travel.